The conchostracan subgenus Orthestheria (Migransia) from the Tacuarembó Formation (Late Jurassic -?Early Cretaceous, Uruguay) with notes on its geological age - Yanbin, Shen (2004)
Conchostracans from the Tacuarembó Formation s.s. of Uruguay are reassigned to the subgenus Orthestheria (Migransia) Chen and Shen. They show more similarities to genera of Late Jurassic age in the Congo Basin and China than to those of Early Cretaceous age. On the basis of the character of the conchostracans, we suggest that the Tacuarembó Formation is unlikely to be older than Late Jurassic. It is probably Kimmeridgian, but an Early Cretaceous age cannot be excluded. This finding is consistent with isotopic dating of the overlying basalts, as well as the age range of recently described fossil freshwater sharks. © 2004 Published by Elsevier Ltd.